Aleitamento materno em crianças nascidas com peso inferior à 2000g até seis Meses de Vida - Bianca Venancio Romanini (2006)
This survey is about a descriptive and longitudinal study from breastfeeding with children born with less than 2000g, in their six months of life, accomplished at Sofia Feldman Hospital. The population studied was of 89 children. These childrens feeding was verified in four moments: at the birth, hospital charging and at the 3rd and 6rd monts of life. It was verified at the moment of charging, this rate being considered satisfactory. The frequencies of only breastfeeding in the 3rd and 6rd months of age were respeccively 40,5% and 4,5%. The rates of breastfeeding found were of 93,3% at the charging and 74,3% in the 6th month of chronological age. The mean duration of mothers breastfeeding was 5,3±1,4 months. From the total of 25 children with less than 1500g when born, 92% were breastfeeding until their hospital charging and 56% from the children, were being breastfeeding at 6 months old. This study shows that ideal situation is far from being reached, in spite of the improvements that have been occurred in relation to the incentive of breastfeeding for children with low weight when they are born.